The Relationship Between Social Assistance Policy and Recipient Behavior in Poverty Alleviation Programs in Limboto District, Gorontalo Regency - Rini Eka Saputri Oktaviani Paputungan; Ellys Rachman; Rukiah Nggilu (Science Tech Group, 2026)
Poverty remains one of the most persistent development challenges in Gorontalo Regency, where poverty rates have consistently exceeded the national and provincial averages over the past five years. This study examined how social assistance policy and recipient behavior jointly relate to poverty alleviation outcomes in Limboto District. A quantitative survey design was employed, with 99 respondents drawn through proportional random sampling from a population of 920 beneficiaries of the Contribution Assistance Program (PBI) across three villages. Data were collected via Likert-scale questionnaires and analyzed using multiple regression. The results show that social assistance policy accounts for approximately 38.9% of the variance in poverty alleviation outcomes, and recipient behavior accounts for 39.1%, indicating that both variables carry roughly equal weight. When examined together, social assistance policy and recipient behavior jointly explain 41.7% of the variation in poverty alleviation, with the remaining 58.3% attributable to other factors. All three relationships are positive and statistically significant. These findings suggest that effective poverty alleviation cannot rest on policy design alone it also depends on how beneficiaries engage with and respond to the assistance they receive. Strengthening targeting accuracy, ensuring consistent program delivery, and fostering productive recipient behavior are therefore complementary, not competing, priorities.